2015
DOI: 10.14814/phy2.12267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic hypoxia on human muscular adaptations to resistance exercise training

Abstract: This study investigated the effect of resistance exercise training performed under systemic hypoxia or normoxia on biochemical and molecular muscular adaptations in healthy male subjects. Our findings demonstrate that resistance training under systemic hypoxia led not only to muscle hypertrophy, but most interestingly, to a greater increase in muscular endurance. This increase in muscular endurance was potentially caused by the increased angiogenesis as determined by capillary‐to‐fiber ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 3 publications
2
24
0
Order By: Relevance
“…showed that muscular endurance was significantly increased under hypoxic exercise training in human skeletal muscle [18]. Consistent with their results, the results of this study showed that hypoxic lip training was effective for increasing both orbicularis oris muscular strength and endurance because both of them were greatly increased after the hypoxic training at T3 (Figs.7 and 8).…”
Section: Effectiveness Of Trainingsupporting
confidence: 90%
“…showed that muscular endurance was significantly increased under hypoxic exercise training in human skeletal muscle [18]. Consistent with their results, the results of this study showed that hypoxic lip training was effective for increasing both orbicularis oris muscular strength and endurance because both of them were greatly increased after the hypoxic training at T3 (Figs.7 and 8).…”
Section: Effectiveness Of Trainingsupporting
confidence: 90%
“…These studies are summarized in [11,17]. However, other investigations using similar training loads but with extended inter-set recovery intervals (90-120 s) have demonstrated no added benefit for training under hypoxia [12,13]. Although it is too early to make definitive recommendations based on only these investigations, we hypothesize that low-and moderate-load IHRT might only provide added benefit when relatively brief inter-set rest periods are used.…”
Section: Conflicting Results Of Ihrt Studiesmentioning
confidence: 95%
“…Theoretically, higher concentrations of hormones increase the likelihood of receptor interactions [36], thereby enhancing the action of these hormones. In particular, increased growth hormone concentrations have been reported following low-load [23] and moderateload [13,24] IHRT. Post-exercise elevations in growth hormone may be mediated by increased lactate and/or hydrogen ion build-up [37].…”
Section: Anabolic Effects Of Metabolic Stressmentioning
confidence: 99%
See 2 more Smart Citations